2002
DOI: 10.1067/mva.2002.123679
|View full text |Cite
|
Sign up to set email alerts
|

Aortic clamping during elective operations for infrarenal disease: The influence of clamping time on renal function

Abstract: Postoperative renal function impairment is rare in this group of patients. If suprarenal clamp duration (renal ischemia time) is brief, patients with normal preoperative creatinine levels exhibit no increase or a marginal increase in BUN or creatinine levels after surgery. Accordingly, suprarenal aortic clamping less than 50 minutes in this patient group appears safe and well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 19 publications
1
75
0
10
Order By: Relevance
“…During cardiac intervention, ischemic renal injury can occur during operative procedures and with the use of contrast media, anesthetics, antibiotics, and diuretics; these are considered risk factors for renal impairment. 16,17 Our previous study of patients with stroke or aneurysm found that 10.4-12% had RAS and impaired kidney function was associated with its presence. 18,19 RAS is an important predictor of kidney function; however, kidney dysfunction is not totally attributable to the presence of RAS.…”
Section: Discussionmentioning
confidence: 99%
“…During cardiac intervention, ischemic renal injury can occur during operative procedures and with the use of contrast media, anesthetics, antibiotics, and diuretics; these are considered risk factors for renal impairment. 16,17 Our previous study of patients with stroke or aneurysm found that 10.4-12% had RAS and impaired kidney function was associated with its presence. 18,19 RAS is an important predictor of kidney function; however, kidney dysfunction is not totally attributable to the presence of RAS.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][12][13][14] Other studies have reported poor renal function with such prolonged ischemia times. 14,15 It would seem that kidneys with tumours amenable to partial nephrectomy may not be subjected to the same global stress as kidneys with major trauma or physiologic events surrounding the death of cadaveric kidney donors and hence may tolerate longer WIT.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, reports show renal function recovery at WIT of 45 to 271 minutes. [3][4][5][6] As advances in laparoscopic surgery continue to evolve, minimally invasive surgical techniques are being applied to increasingly complex surgical procedures. One of the limitations for laparoscopic partial nephrectomy has been the duration of renal hilar clamp time required to remove the tumour, secure hemostasis and repair the collecting system by intracorporal suturing, which may easily take more than 30 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…E. Wahlberg и соавт. [16] подчеркнули, что наиболее важ-ным фактором риска ишемического повреждения являет-ся продолжительность пережатия аорты проксимальнее почечного трансплантата. Они пришли к выводу, что пе-режатие аорты менее 50 мин является безопасным, но на-рушения функции почки в предоперационном периоде и гипотензия во время операции могут привести к ишеми-ческим повреждениям даже при кратковременной ише-мии.…”
Section: заключениеunclassified